PROGRAM MATLAB UNTUK MEDIA ALAT PENGANALISA PERCOBAAN FISIKA BAGI MAHASISWA STMIK BINA PATRIA - Wijaya Widjanarka Natasaputra; Sukris Sutiyatno (TRANSFORMASI, 2021)
The Matlab application program is often used as a data processing tool as well as tables, 2 or 3 dimensional graphs. Practicum activities for Physics subjects in general, the results of physics experiments are written directly into the experimental report. In practicum activities, the campus tries to make or design a Matlab application program for practicum activities. The results are processed using a computer application program, before being recorded in the report. The Matlab application program is often used as a tool for processing data and tables, 2 and 3-dimensional graphs. Students are given experimental data on Physics about this Matlab program, then analyzed and presented in graphical form and others. The result was that after being given additional lessons in the Matlab program, students processed the results of the physics experiment, and found out if there were experimental data that needed to be improved. Equipped with a tutor textbook. Keywords: Matlab, Physics Experiment, 2D 3D graphics.